Implementasi Kebijakan Retribusi Parkir Kota Semarang - Utami, Sindy Fitria; Hariani, Dyah; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The convening of a parking levy aims to increase revenue (PAD) and keep order and comfort of the vehicle. These objectives can be achieved through the implementation of effective processes that can be seen from the appropriateness of the policy, the accuracy of implementation, the target precision, accuracy and precision of the process environment. Parking charges policy implementation process in achieving its objectives can not be separated from the factors that support and hinder. Based on the theory of Edwards III several factors that support and hinder the form of objective / outcome, Communications and Resources Based on the existing obstacles in the implementation of policies parking fees the city, the authors provide recommendations include: (1) increasing the number of staff accordingly (2) formal socialization to parking attendants so that the information can be the same (3) increase the budget allocation policy (4) add a vehicle to facilitate the mobilization.